Analysis of Earth Resistance Effect on The TT- Grounding System Against Electric Shock - Sunarto, Sunarto; Sudrajat, Sudrajat; Hikmat, Yudi Prana (Eksergi, 2022)
Abstract - Based on the General Requirements for the PUIL 2011 (Persyaratan Umum Instalasi Listrik 2011), there are three types of earthing systems, namely the TN system, the TT system, and the IT system.These three types of earthing function to prevent electric shock that is harmful to humans. Earthing part of the equipment namely open conductive part on the TT system is installed separately, where the open conductive part of electrical equipment is connected directly to the earth in order to limit the amount of voltage between the open conductive part and the earth to the allowable limit if a leakage current is caused due to a failure insulation.The action taken to minimize the occurrence of indirect touch stress is to use an earthing system with the aim of: Conducting current from the metal parts of the equipment that flows through the leakage to the ground through the earth channel, Minimize potential differences between the metal parts of the equipment and the ground so that it is not dangerous if touched.Earthing resistance value on the TT system greatly affects the magnitude of the touch voltage that occurs at open conductive part due to a leakage current due to insulation failure. If the resistance value of the earth electrode exceeds the allowable standard, it can cause the touch voltage that occurs in the open conductive part to exceed the maximum standard based on the PUIL 2011 standard and there is no safety of the MCB or ELCB, it will be dangerous if touched by humans because it can cause damage to the human body and can cause death.